Comparative analysis of liquid based and conventional cytology smears in fine needle aspirates from breast lesions - Vasundhara Sharma; Veena Gupta; Padam Parmar; Promil Jain; Deepak Thakran; Rajeev Sen (Journal of Cytology, 2019)
Context: Liquid-based cytology (LBC) is being extensively used for the evaluation of both gynecological and non-gynecological specimens. Suspension of cells in monolayer makes better morphological assessment possible. Along with this, inherent morphological changes such as altered, reduced, or lost background material, fragmented cell clusters, smaller cell size, nucleolar prominence, etc., need to be considered. Aim: Present study was aimed at comparative evaluation of utility of LBC versus conventional smear (CS) in assessing breast lesions and whether it can be used as an alternative to conventional preparation. Settings and Design: Present study was a prospective study in which 75 cases of breast fine-needle aspiration cytology from patients with palpable breast lumps constituted the study group. Material and Methods: The first pass was used for CS and LBC; a second pass was given. The representative CS and LBC smears were compared using several criteria. Statistics: Each feature was scored individually and evaluated statistically using Wilcoxon's signed rank test on the SPSS program. Results: A statistically significant difference was found in informative background and background blood-debris, whereas the difference was not statistically significant in other features such as cellularity, cytoarchitectural pattern, presence of monolayer, and nuclear and cytoplasmic details. Conclusion: LBC is a promising technique in the field of cytology. It has the potential to decrease the number of slides screened per case and decrease the turn-around-time.